Sun Tzu and the art of business - McNeilly, Mark (Oxford University Press, 1996)
Here are really two books in one: McNeilly's synthesis of Sun Tzu's ideas into six strategic principles for the business executive, plus the entire text of Samuel B. Griffith's popular translation of The Art of War. Within, McNeilly explains how to gain market share without inciting competitive retaliation, how to attack a competitor's weak points, and how to maximize the power of market information for competitive advantage. He also demonstrates the value of speed, preparation, and secrecy in throwing the competition off-balance, employing strategy to beat the competition, and the need for character in successful leaders. In his final chapter, McNeilly presents a practical method to put Sun Tzu and The Art of Business into practice